CHADS2 and CHA2DS2-VASc scores as predictors of platelet reactivity in acute coronary syndrome. Issue 4 (April 2021) - Asher, Elad; Abu-Much, Arsalan; Bragazzi, Nicola L.; Younis, Anan; Younis, Arwa; Masalha, Eyas; Goldkorn, Ronen; Mazin, Israel; Fefer, Paul; Barbash, Israel M.; Segev, Amit; Beigel, Roy; et al.
Highlights: CHADS2 and CHA2DS2-VASc scores are known to predict stroke in atrial fibrillation. High platelet reactivity is associated with high risk for ischemic events in acute coronary syndrome. We found a direct correlation between CHADS2, CHA2DS2-VASc, and platelet reactivity. Patients with low CHADS2 and CHA2DS2-VASc had optimal platelet reactivity. Patients with high CHADS2 and CHA2DS2-VASc had high platelet reactivity. Abstract: Background: Platelet function testing (PFT) in patients treated with P2Y12 inhibitors has been widely evaluated for the prediction of stent thrombosis, myocardial infarction, and bleeding events following percutaneous coronary intervention (PCI) in acute coronary syndrome (ACS). Thus, PFT-guided treatment could positively affect patient outcomes. Data regarding clinical parameters for predicting platelet reactivity in ACS patients are limited. Therefore, our study aims to evaluate CHADS2 and CHA2DS2-VASc scores as predictors for platelet reactivity in ACS patients. Methods: Two hundred and ninety-one consecutive patients who underwent PCI and were treated with aspirin and clopidogrel due to ACS were tested for their CHADS2, CHA2DS2-VASc scores and platelet reactivity using adenosine diphosphate (ADP)-induced aggregation (conventional aggregometry). Patients were classified into groups according to their CHADS2 and CHA2DS2-VASc scores. Low-risk group (0–1 score) for CHADS2 and CHA2DS2-VASc scores and high-risk group (2–6, 2–9) for CHADS2 and CHA2DS2-VASc scores, respectively. Furthermore, platelet reactivity in each group were compared (low CHADS2 group vs high CHADS2 group, and low CHA2DS2-VASc vs high CHA2DS2-VASc). Platelet reactivity was defined as low platelet reactivity (<19 U), optimal platelet reactivity [(OPR); 19–46 U], and high on-treatment platelet reactivity [(HPR); >46 U]. Thereafter receiver operating characteristic curve analysis was conducted to verify whether CHADS2 and CHA2DS2-VASc scores could predict platelet reactivity. Results: Low CHADS2 and CHA2DS2-VASc scores were significantly correlated with lower mean platelet ADP-induced aggregation as compared with high CHADS2 and CHA2DS2-VASc scores [45.5 U (± 16) vs. 54.8 U (±15) and 44.2 U (±16) vs. 51.0 U (±17), respectively, p = 0.01 for both]. Conclusion: In ACS patients treated with clopidogrel following PCI, high CHADS2 and CHA2DS2-VASc scores correlated with HPR and lower scores correlated with OPR. Further studies are needed to evaluate our findings' clinical implications.